Hubungan Sarana dan Prasarana terhadap Minat Belajar Mata Pelajaran PJOK Siswa SMP Bhakti Praja Kebumen - Mokhamad Parmadi; Heri Yulianto (Journal on Education, 2024)
This research was motivated by observations made by researchers regarding student interest in implementing physical education learning at Bhakti Praja Middle School in Kebumen Regency. Many influencing factors include the physical education facilities and infrastructure available at the school. This research aims to determine the facilities and infrastructure and interest in learning physical education of Bhakti Praja Middle School students in Kebumen Regency. This type of research is descriptive quantitative and correlational. The instrument used is a questionnaire, the data collection technique is observation and documentation. The population of this research is all Bhakti Praja Middle School students in Kebumen, totaling 157 students for the 2023/2024 academic year. This research used a sample of 10% of Bhakti Praja Middle School students, namely 76 students. The sampling technique uses random sampling. Based on the results of data analysis of observations of physical education facilities and infrastructure at Bhakti Praja Middle School in Kebumen Regency 2023/2024, it is known that the number of physical education facilities and infrastructure is in the ideal category for the number of facilities and infrastructure with a value of 80% and with a total percentage of own ownership of 95% as well as for general ownership 5%. And the results of the interest questionnaire based on respondents' responses can be seen that 3.94% of students have very good interest, 35.52% of students have good interest, 31.57% of students have sufficient interest, 21.05% of students have poor interest, 7, 89% of students have very little interest. Based on the results of the correlation and reliability test analysis, it was found that N data was 76 people, the correlation was 1 and Cronbach's Alpha was 806. Facilities and infrastructure have a big influence on students' interest in learning at Bhakti Praja Middle School, Kebumen.